Heart failure and sleep related breathing disorders: Data from PROMISES (Progetto Multicentrico Italiano Sonno e Scompenso Cardiaco) study. (15th November 2018) - Lombardi, Carolina; Faini, Andrea; La Rovere, MariaTeresa; Fanfulla, Francesco; Mattaliano, Paola; Caravita, Sergio; Contini, Mauro; Agostoni, Piergiuseppe; Perrone-Filardi, Pasquale; Parati, Gianfranco; ,
Abstract: Background: In heart failure (HF) sleep problems and sleep-related breathing disorders are frequently reported and are associated with poor prognosis. However, only few large clinical studies have investigated this issue in heart failure through breathing pattern analysis by polysomnography. Methods and results: 370 HF patients, with either moderate-severe reduced ejection fraction or with clinical decompensation, consecutively referred to 10 participating cardiology centers, have been enrolled in the PROMISES Study, an Italian project aimed at generating a large, multidisciplinary database of anthropometric, clinical, echocardiographic and sleep data, the last derived from overnight unattended cardio-respiratory polysomnography in HF patients. Obstructive sleep apnea was the most frequent form of sleep related breathing disorders observed in our cohort (35.4% with an AHI cutoff of 15). The possible determinants of sleep related breathing disorders were analyzed through stepwise logistic regression analysis and two multivariate models showing that a markedly reduced left ventricular ejection fraction was the most important factor associated with central sleep apneas (OR = 7.7 for AHI cutoff = 15 and LVEF ≤ 35%) together with male gender and increasing age. Conventional risk factors for obstructive sleep apnea did not identify HF patients affected by this condition. Conversely, a greater neck circumference was associated with an increased risk for central apneas. Conclusions: Our paper offers a deeper insight into the features of SRBD and its determinants in HF patients, leading in turn to a better clinical management of these comorbid patients. Highlights: PROMISES Study is an Italian multidisciplinary database in HF patients. Determinants of sleep related breathing disorders were analyzed in HF patients. Insight into the features of SRBD and its determinants in HF patients The conventional risk factors for OSA were not able to predict this condition in HF.